Caves - Pettiford, Rebecca (Minneapolis, MN : Jump!, 2018)
Carefully leveled text and vibrant photographs introduce early readers to caves.
A hole in the Earth -- Inside a cave -- Mammoth cave.
Includes index.
2.3
K-3
500L
Keywords: Caves -- Juvenile literature; Landforms -- Juvenile literature; Caves; Landforms